Myanmar Report on Observance of Standards and Codes : Accounting and Auditing Module - World Bank (Washington, DC, 2017)
Since launching fundamental political and economic reforms in 2011, Myanmar has been undergoing a major transformation aimed at increasing openness, empowerment and inclusion. The economic transition has witnessed an acceleration in growth, buoyed by improved macroeconomic management, increased gas production and exports, and stronger performance in the non-gas sectors as the economy opened up. Medium-term economic growth is projected to average 7.1 percent per year. The new Government’s economic objectives envisage Myanmar’s economy becoming more competitive and with the ability to attract increased foreign direct investment. The objectives include the development of an integrated capital market and a modern financial sector. A fundamental foundation for any market-based economy is high quality financial reporting and auditing practices. This plays a vital role in promoting improved transparency and accountability thereby ensuring a level playing field and promoting investor confidence. The Reports on the Observance of Standards and Codes (ROSC) are a joint World Bank and International Monetary Fund (IMF) initiative that helps member countries strengthen their financial systems by improving compliance with internationally recognized standards and codes. The ROSC was developed in the wake of the financial crisis of the late 1990s as part of a series of measures to strengthen the international financial architecture. The global financial community believed the implementation of internationally recognized standards and codes will provide a framework to strengthen domestic institutions, identify potential vulnerabilities, and improve transparency.